Diabetes mellitus with a duration of 26 years combined with IgA nephropathy: A case report and literature review - Gou, Yan-Li; Zhang, Ya-Pu; Xu, Yang; Li, Jian-Dong; Huang, Yang; Chen, Hang (Frontiers in Endocrinology, 2022)
Background: The incidence of diabetes mellitus (DM) in China is increasing yearly and has become a major problem plaguing national public health. The diagnosis of diabetic kidney disease (DKD) is based primarily on clinical criteria, and most patients do not receive a formal evaluation by renal biopsy; thus, misdiagnosis and underdiagnosis are common. The incidence of non-diabetic kidney disease (NDKD) is also higher in those with DM. To date, many cases of IgA nephropathy (IgAN) among those with DKD have been reported, while cases of IgAN in patients with long-duration DM who did not develop DKD are less commonly reported. Case description: A 70-year-old male patient with a diabetes duration of 26 years had proteinuria for one year. The clinical manifestations of nephrotic syndrome and IgAN were confirmed by renal biopsy. The patient received targeted treatment for three years with partial alleviation of proteinuria. Conclusion: Renal biopsy might aid in the definitive diagnosis of DKD, NDKD, and NDKD combined with DKD. Precise therapy based on renal pathology might help to improve outcomes in the kidney.